1976
DOI: 10.1038/icb.1976.30
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Inter‐epidemic Infection of Feral Pigs in New South Wales With Murray Valley Encephalitis Virus

Abstract: Summary The sera of 617 feral pigs, collected from three widely separated areas of northern and central New South Wales, were examined for antibody to Murray Valley encephalitis (MVE) virus and to Ross River virus. Haemagglutination‐inhibition (HI) antibody was detected to MVE in 58% of sera and to Ross River virus in 15% of sera. Neutralization tests suggested that the MVE HI antibody resulted from infection with MVE virus in the summers of 1971–1972 and 1972–1973 when the virus was not known to he active in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…3a and b) to each other and their differences from other Australian isolates. There is some serological evidence to suggest that MVE was present in New South Wales prior to 1974 (Doherty et al, 1972;Gard et aL, 1976), although actual isolations were not made. At the same time (1973), another Australian flavivirus, Kunjin virus, was isolated from C. annulirostris in western New South Wales (Gard et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and b) to each other and their differences from other Australian isolates. There is some serological evidence to suggest that MVE was present in New South Wales prior to 1974 (Doherty et al, 1972;Gard et aL, 1976), although actual isolations were not made. At the same time (1973), another Australian flavivirus, Kunjin virus, was isolated from C. annulirostris in western New South Wales (Gard et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…The case fatality rate can be high (Anderson, 1954), There were unprecedented climatological conditions preceding this last epidemic, and it has been suggested that heavy rainfall and extensive flooding may be important factors in the dissemination of MVE from the enzootic areas in the north of Australia to these temperate regions (Miles & Howes, 1953;Anderson, 1954). However, there is also some evidence to suggest that MVE may circulate at a low level in the south-east of Australia during inter-epidemic periods (Gard et al, 1976). In the Pilbara area of Western Australia, virus activity occurs every 3 to 4 years (unpublished observations) and it is thought that virus may be spread from the Kimberley region via a narrow coastal belt (Stanley, 1979).…”
Section: Introduction Murray Valley Encephalitis Virus (Mve) Is a Memmentioning
confidence: 99%
“…It is widely accepted that both viruses are enzootically maintained in tropical northern Australia. Serological surveys suggest that birds, particularly waterbirds, and feral pigs are important natural hosts (Gard et al, 1976;Doherty, 1977;. The major arthropod vector is Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there was little difficulty in distinguishing between MVE and KUN as the likely antibody-inducing agent in a retrospective study of feral pig sera from northern N.S.W. which was carried out in this laboratory (Gard et al, 1976). In the present series both constant serum-virus dilution and constant virus-serurti dilution plaque reduc-tion neutralization tests on Vero cell monolayers failed to give clear differentiation between MVE and KUN in almost half the sera tested.…”
Section: Specificity Of Reactionsmentioning
confidence: 73%
“…The two viruses are closely related, and there is a "gross morphologic and biologic resemblance" between the two primary vectors, Cx annulirostris and Cx tritaeniorhynchus (Reeves et al, 1954). The domestic pig has been shown to be crucially involved in epidemics of Japanese encephalitis (Scherer, Moyer, Izumi, Gresser and McCown, 1959;Detels et al, 1976) and there is serological evidence of frequent infection of feral pigs with MVE virus in northern New South Wales (Gard et al, 1976). However, the most intriguing potential parallel is the relationship between the two viruses and the black-crowned night heron (Nycticorax nycticorax) and the rufous or nankeen night heron (Nycticorax calcndonicus).…”
Section: Specificity Of Reactionsmentioning
confidence: 99%